Effect of iron in the levels of dopamine and acetylcholine and oxidative stress indicators in male rats treated with manganese chloride - R. Ibrahim, Ihsan; M. kadhem, Wejdan (Al-Qadisiyah Journal of Pure Science, 2017)
The aim of this study was to determine the toxic effects of manganese in the brain as well as assess the role that could be played by iron to reduce the toxic effects of manganese in male rats . In this experiment (21) animals of male rats were divided randomly into three groups , the first group(C): it as control group was given saline physiological and given bush normal , the second group( G1): that given manganese chloride concentration of 150 mg / kg of body weight per day , the third group( G2): which given manganese chloride concentration of 150 mg / kg of body weight was also given ferrous sulfate concentration of 30 mg / kg of diet per day. After the end of experiment the following parameters were studied: neurotransmitters included dopamine and acetylcholine in the brain antioxidants included Glutathione and MDA in the brain and superoxide dismutase and Catalase in serum . The results showed that given manganese chloride in rats has led to a significant decrease (P <0.05) in the level of dopamine in the brain with significant increase (P <0.05) in the level of acetylcholine in the brain . Also these results were showed a significant decrease (P <0.05) in the level of Glutathione in the brain , accompanied by a significant increase (P <0.05) in the level of MDA in the brain. While there was a significant decrease (P <0.05) in SOD concentration and CAT concentration in serum . Animals that given of ferrous sulfate simultaneously with manganese chloride in groups G2 has led to obtain a significant improvement in studied parameters compared with the group G1 which given manganese chloride and soon sometimes for control group.